Impact resistant glass-polymer laminate and sensor incorporating same

By using compressive stress glass-polymer laminate in LiDAR systems, the problem of windows being susceptible to impact damage is solved, achieving higher impact resistance and optical retention.

CN119136978APending Publication Date: 2024-12-13CORNING INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380036992.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-28
Filing Date
2023-04-19
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Window in traditional LiDAR systems are susceptible to impact damage, resulting in laser beam scattering and reflection, affecting the effectiveness of the system.

Method used

Using a glass-polymer laminate consisting of two glass base layers and one polymer layer, the glass base layer generates compressive stress by heating and cooling at curing temperature, improving the impact performance of the glass, and passing through relatively thin outer glass The asymmetric structure of the base layer and the thicker inner glass base layer reduces the impact-induced defect propagation.

Benefits of technology

It significantly improves the impact resistance of the window, reduces the defects and scattering caused by the impact, maintains the optical performance, and enhances the stability and effectiveness of the LiDAR system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136978A_ABST
    Figure CN119136978A_ABST
Patent Text Reader

Abstract

Glass-based articles including a first glass-based layer, a second glass-based layer, and a polymer layer disposed between the first glass-based layer and the second glass-based layer are described. The first glass-based layer and the second glass-based layer may include coefficients of thermal expansion that differ from each other by at least 0.5 ppm / DEG C. The first glass-based layer may include a thickness less than or equal to 300 [mu] m, while the second glass-based layer may include a thickness greater than 2.0 mm. The second glass-based layer may provide structural rigidity to the article, while the first glass-based layer may make impact-induced damage less significant and less likely to negatively impact optical performance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] priority

[0002] This application claims the benefit of priority under 35 U.S.C. §119 to U.S. Provisional Patent Application No. 63 / 335,827, filed on April 28, 2022, the contents of which are the basis of this application and are incorporated herein by reference in their entirety. Technical Field

[0003] The present application relates to glass-polymer laminates, and more particularly to glass-polymer laminates for use in sensing systems such as light detection and ranging ("LiDAR") systems. Background Art

[0004] Light detection and ranging ("LiDAR") systems include a laser and a sensor. The laser emits a laser beam that may be reflected from an object, and the sensor detects the reflected laser beam. The laser beam is pulsed or otherwise distributed over a radial range to detect objects within the entire field of view. Information about the object can be deciphered from the properties of the detected reflected laser beam. The distance of the object from the laser beam can be determined based on the flight time from the emission of the laser beam to the detection of the reflected laser beam. If the object is moving, the path and speed of the object can be determined based on the displacement of the radial position of the emitted laser beam that is reflected and detected as a function of time, and based on Doppler frequency measurements.

[0005] Vehicles are one possible application for LiDAR systems, where they provide spatial mapping capabilities to enable assisted, semi-autonomous, or fully autonomous driving. Traditionally, laser emitters and sensors are mounted on the top of the vehicle or on the lower front of the vehicle. Lasers that emit electromagnetic radiation at wavelengths outside the visible light range (such as at or near 905 nanometers or 1550 nanometers) are considered for vehicle LiDAR applications. In order to protect the laser and sensor from impacts with rocks and other objects, a window is placed between the laser and sensor and the external environment within the line of sight of the laser and sensor. However, there is a problem that impacting rocks and other objects can scratch the window and cause other types of damage to it, which causes the window to scatter the emitted and reflected laser beams, thereby compromising the effectiveness of the LiDAR system. Summary of the invention

[0006] Aspect (1) of the present disclosure relates to an article comprising: a first glass substrate having a thickness t G1 and the coefficient of thermal expansion CTE G1 ; A second glass substrate having a thickness t G2 and the coefficient of thermal expansion CTE G2; and a first polymer layer, the first polymer layer is disposed between the first glass substrate and the second glass substrate, the first polymer layer having a thickness t P1 and the coefficient of thermal expansion CTE P1 , wherein: the first glass substrate includes a compressive stress, |CTE G1 -CTE G2 |>0.5ppm / ℃,t G2 Greater than 2.0 mm, and t G1 Less than or equal to 300μm.

[0007] Aspect (2) of the present disclosure relates to the article as described in aspect (1), wherein: G1 Less than or equal to 200 μm, and t G2 Greater than 2.5mm and less than or equal to 3.8mm.

[0008] Aspect (3) of the present disclosure relates to the article of aspect (2), wherein: the compressive stress is greater than or equal to 5 MPa and less than or equal to 40 MPa, and the second glass layer includes a tensile stress less than or equal to 10 MPa.

[0009] Aspect (4) of the present disclosure relates to the article as described in any one of aspects (1) to (3), wherein: G1 Less than or equal to 150μm, and t G2 Greater than or equal to 2.5 mm and less than or equal to 3.8 mm.

[0010] Aspect (5) of the present disclosure relates to the article of any one of aspects (1)-(5), wherein the first glass substrate is formed of a glass that exhibits abnormal fracture behavior when subjected to a Vickers diamond indenter test.

[0011] Aspect (6) of the present disclosure relates to an article as described in any of aspects (1)-(5), wherein the first glass substrate is not chemically strengthened and the compressive stress is generated by laminating the first glass substrate to the second glass substrate via the first polymer layer at a curing temperature that differs from the use temperature of the article by at least 20°C.

[0012] Aspect (7) of the present disclosure relates to the article as described in aspect (6), wherein CTE G1 <CTE G2 , and the curing temperature is greater than or equal to 30°C.

[0013] Aspect (8) of the present disclosure relates to the article as described in any one of aspects (1)-(7), wherein the second glass substrate comprises soda-lime glass.

[0014] Aspect (9) of the present disclosure relates to the article as described in aspect (1), further comprising: a third glass substrate having a thickness t G3 and the coefficient of thermal expansion CTE G3 , and a first polymer layer disposed between the first glass substrate and the third glass substrate, the first polymer layer having a thickness t P2 and the coefficient of thermal expansion CTE P2 , wherein: the second glass substrate includes a second compressive stress, |CTE G2 -CTE G3 |>0.5ppm / ℃, and t G3 Less than or equal to t G2 20% of.

[0015] Aspect (10) of the present disclosure relates to the article as described in aspect (9), wherein t G1 and t G3 Both are less than or equal to 200 μm.

[0016] Aspect (11) of the present disclosure relates to the article as described in aspect (10), wherein t G2 Greater than or equal to 2.5 mm and less than or equal to 3.8 mm.

[0017] Aspect (12) of the present disclosure relates to the article of aspect (9), wherein the first glass substrate and the second glass substrate are formed of the same glass composition such that CTE G1 =CTE G3 .

[0018] Aspect (13) of the present disclosure relates to the article as described in aspect (9), wherein t G1 =t G3 , and t G1 and t G3 Both are less than or equal to 150μm.

[0019] Aspect (14) of the present disclosure relates to the article as described in any one of aspects (1) to (13), wherein the total thickness of the article is less than or equal to 4.0 mm.

[0020] Aspect (15) of the present disclosure relates to the article of any one of aspects (1) to (14), wherein the article does not break when the first glass substrate is impacted by a Vickers diamond indenter traveling at a speed of 1000 mm / sec.

[0021] Aspect (16) of the present disclosure relates to an article as described in any one of aspects (1)-(15), wherein at least one of the first glass substrate and the second glass substrate is warped due to a process of laminating the first glass substrate to the second glass substrate via the first polymer layer.

[0022] Aspect (17) of the present disclosure relates to a sensor comprising: a housing; a detection element disposed in the housing; and a window attached to the housing so as to surround an interior of the housing, wherein the window comprises: a first glass substrate having a thickness t G1 and the coefficient of thermal expansion CTE G1 ; A second glass substrate having a thickness t G2 and the coefficient of thermal expansion CTE G2 ; and a first polymer layer, the first polymer layer is disposed between the first glass substrate and the second glass substrate, the first polymer layer having a thickness t P1 and the coefficient of thermal expansion CTE P1 , wherein: the first glass substrate includes a compressive stress greater than or equal to 5 MPa and less than or equal to 40 MPa, the compressive stress being determined by CTE G1 With GTE G2 The difference between the two is generated, t G1 Less than or equal to 300μm, and t G2 Greater than 2.0mm.

[0023] Aspect (18) of the present disclosure relates to the sensor as described in aspect (17), wherein: G1 Less than or equal to 200 μm, and t G2 Greater than or equal to 2.5 mm and less than or equal to 3.8 mm.

[0024] Aspect (19) of the present disclosure relates to a sensor as described in any of aspects (17)-(18), wherein: the first glass substrate is formed of a glass that exhibits abnormal fracture behavior when subjected to a Vickers diamond indenter test, and the first glass substrate forms an outer surface of the window, which is exposed to the environment outside the housing.

[0025] Aspect (20) of the present disclosure relates to a sensor as described in any of aspects (17)-(19), wherein the first glass substrate is not chemically strengthened and the compressive stress is generated by laminating the first glass substrate to the second glass substrate via the polymer layer at a curing temperature greater than or equal to 50°C.

[0026] Aspect (21) of the present disclosure relates to the sensor as described in any one of aspects (17) to (20), further comprising: a third glass substrate having a thickness t G3 and the coefficient of thermal expansion CTE G3 , and a second polymer layer disposed between the first glass substrate and the third glass substrate, the first polymer layer having a thickness t P2 and the coefficient of thermal expansion CTE P2 , wherein: the second glass substrate includes a second compressive stress, |CTE G2 -CTE G3 |>0.5ppm / ℃, and t G3 Less than or equal to t G2 10% of.

[0027] Aspect (22) of the present disclosure relates to the sensor as described in aspect (21), wherein t G1 and t G3 Both are less than or equal to 200 μm.

[0028] Aspect (23) of the present disclosure relates to the sensor as described in aspect (22), wherein t G2 Greater than or equal to 2.5 mm and less than or equal to 3.8 mm.

[0029] Aspect (24) of the present disclosure relates to the sensor as described in aspect (21), wherein the first glass substrate and the third glass substrate are formed of the same glass composition so that CTE G1 =CTE G3 .

[0030] Aspect (25) of the present disclosure relates to a sensor as described in any one of aspects (21) to (24), wherein t G1 =t G3 , and t G1 and t G3 Both are less than or equal to 150μm.

[0031] Aspect (26) of the present disclosure relates to a method comprising: disposing a first polymer layer between a first glass substrate and a second glass substrate, wherein the thickness of the first glass substrate is less than or equal to 15% of the thickness of the second glass substrate, and wherein the thickness of the second glass substrate is greater than 2.0 mm; Cand curing the first polymer layer in an environment under 0.5 ppm / ° C. to form an article; and after the curing step, returning the temperature of the first glass substrate and the second glass substrate to a use temperature greater than or equal to 0° C. and less than or equal to 30° C., wherein: the first thermal expansion coefficient of the first glass substrate differs from the second thermal expansion coefficient of the second glass substrate by at least 0.5 ppm / ° C., and T C The difference from the use temperature is at least 20° C., so that returning the temperature to the use temperature causes the first glass substrate to have a compressive stress greater than or equal to 5 MPa and less than or equal to 40 MPa.

[0032] Aspect (27) of the present disclosure relates to the method as described in aspect (26), further comprising: before the curing step, disposing a second polymer layer between the first glass substrate and a third glass substrate, wherein the thickness of the third glass substrate is less than or equal to 10% of the thickness of the second glass substrate.

[0033] Aspect (28) of the present disclosure relates to a method as described in aspect (27), wherein the third coefficient of thermal expansion of the third glass substrate differs from the second coefficient of thermal expansion by at least 0.5 ppm / °C, such that after returning to the use temperature, the third glass substrate includes a second compressive stress.

[0034] Aspect (29) of the present disclosure relates to the method as described in any one of aspects (27)-(28), wherein the third glass substrate and the first glass substrate comprise the same thickness and are formed of the same glass composition.

[0035] Aspect (30) of the present disclosure relates to a method as described in any one of aspects (27)-(29), wherein the first glass substrate and the third glass substrate are both formed of glass that exhibits abnormal fracture behavior when subjected to a Vickers diamond indenter test.

[0036] Additional features and advantages will be set forth in the following detailed description, and those skilled in the art will readily appreciate in part these features and advantages from this detailed description, or recognize these features and advantages by practicing the embodiments described herein, including the following detailed description, claims, and drawings.

[0037] It is to be understood that the foregoing general description and the following detailed description are merely exemplary and are intended to provide an overview or framework for understanding the nature and character of the claims. The accompanying drawings are included to provide a further understanding and are incorporated into and constitute a part of this specification. The drawings illustrate one or more embodiments and together with the description serve to explain the principles and operation of the various embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1is a side view of a vehicle with a LiDAR mounted on the top and a LiDAR system mounted on the front according to one or more embodiments of the present disclosure;

[0039] Figure 2 According to one or more embodiments of the present disclosure Figure 1 A conceptual diagram of one of the LiDAR systems, including the cover window.

[0040] Figure 3 According to one or more embodiments of the present disclosure, Figure 2 A cross-sectional view of a glass-polymer laminate in a window of FIG.

[0041] Figure 4 According to one or more embodiments of the present disclosure, Figure 2 A cross-sectional view of a second embodiment of a glass-polymer laminate in a window of FIG.

[0042] Figure 5 According to one or more embodiments of the present disclosure, Figure 2 A cross-sectional view of a curved glass-polymer laminate in a window of FIG.

[0043] Figure 6 are measured optical transmission spectra of various monolithic glass substrates and glass-polymer laminates according to one or more embodiments of the present disclosure;

[0044] Figure 7 are images of a first example glass-polymer laminate and a second example glass-polymer laminate including two relatively thick glass layers and one polymer layer after being subjected to a sharp impact test according to one or more embodiments of the present disclosure;

[0045] Figure 8 are images of a third example glass-polymer laminate and a fourth example glass-polymer laminate including a relatively thick inner glass layer, a polymer layer, and a relatively thin outer glass layer after being subjected to a sharp impact test according to one or more embodiments of the present disclosure;

[0046] Fig. 9 are images of a fifth example glass-polymer laminate and a sixth example glass-polymer laminate after undergoing a sharp impact test according to one or more embodiments of the present disclosure, wherein the fifth example includes a relatively thick inner glass layer surrounded by two relatively thin outer glass layers, and the sixth example includes two relatively thin outer glass layers disposed on one side of the relatively thick inner glass layer;

[0047] Fig.10is an image of a test setup for dynamic load impact testing of an example glass-polymer laminate according to one or more embodiments of the present disclosure;

[0048] Fig.11 is an image of a sample of a seventh example glass-polymer laminate according to one or more embodiments of the present disclosure after undergoing impact testing at multiple impact velocities;

[0049] Fig.12 is an image of a sample of an eighth example glass-polymer laminate according to one or more embodiments of the present disclosure after undergoing impact testing at multiple impact velocities;

[0050] Fig.13 is an image of a sample of a ninth example glass-polymer laminate according to one or more embodiments of the present disclosure after undergoing impact testing at multiple impact velocities;

[0051] Fig.14 are images of a sample of a tenth example glass-polymer laminate according to one or more embodiments of the present disclosure after undergoing impact testing at multiple impact velocities;

[0052] Fig.15 is an image of a sample of an eleventh example glass-polymer laminate according to one or more embodiments of the present disclosure after undergoing impact testing at a plurality of impact velocities; and

[0053] Fig.16 are images of a sample of a twelfth example glass-polymer laminate according to one or more embodiments of the present disclosure after undergoing impact testing at multiple impact velocities. DETAILED DESCRIPTION

[0054] Reference will now be made in detail to the present embodiments, examples of which are illustrated in the accompanying drawings. Where possible, the same reference numerals will be used throughout the drawings to refer to the same or similar parts. With general reference to the drawings, impact-resistant glass-polymer laminates are described herein. Impact-resistant glass-polymer laminates can be used in a variety of applications, including, but not limited to, sensor windows. For example, the glass-polymer laminates described herein can be used to cover windows for cameras or LIDAR sensor systems associated with vehicles such as automobiles, locomotives, ships, aircraft, satellites. Compared to certain existing forms of covering materials for cover window applications (such as chemically strengthened glass, glass-glass laminates, plastics), glass-polymer laminates have greater resistance to damage from commonly encountered impact events (such as rocks, stones, or sandblasting associated with the exterior of the vehicle). In particular, the glass-polymer laminates described herein may include two or more glass substrates, wherein at least two adjacent glass substrates differ from each other in coefficient of thermal expansion ("CTE") by at least 0.5 ppm / °C. The adjacent glass substrates are separated from each other by a polymer layer. During construction of the glass-polymer laminates described herein, a stack consisting of at least a first glass substrate, a first polymer layer, and a second glass substrate is heated to a curing temperature that is different from the expected use temperature of the laminate (which is associated with typical operating conditions of the sensor). While at the curing temperature, the polymer layer is cured (e.g., either by applying radiation thereto or via a temperature treatment). Subsequently, the stack is heated or cooled to a use temperature such that the CTE difference between the glass substrates results in a compressive stress in one of the glass substrates. The compressive stress beneficially improves the impact performance of the glass substrate, thereby providing advantageous performance characteristics for various sensors or other applications that require resistance to damage from impact events.

[0055] In various aspects, the glass-polymer laminates described herein can be implemented as cover windows for various sensor applications, wherein at least one glass substrate having compressive stress therein is positioned to face the external environment of the sensor as an outer glass substrate. It has been found that from an impact performance perspective, it is particularly advantageous when the thickness of the outer glass substrate is substantially less than that of the inner glass substrate (which is positioned, for example, closer to the sensor than the outer glass substrate). In an embodiment, the thickness of the outer glass substrate is less than or equal to 20% (e.g., less than or equal to 19%, less than or equal to 18%, less than or equal to 17%, less than or equal to 16%, less than or equal to 15%, less than or equal to 14%, less than or equal to 13%, less than or equal to 12%, less than or equal to 11%, less than or equal to 10%, less than or equal to 9%, less than or equal to 8%, less than or equal to 7%, less than or equal to 6%, less than or equal to 5%, less than or equal to 4%, less than or equal to 3%) of the thickness of the inner glass substrate. For example, in an embodiment, the thickness of the outer glass substrate is greater than or equal to 10 μm and less than or equal to 300 μm, while the thickness of the inner glass substrate is greater than 2.0 mm (e.g., greater than or equal to 2.1 mm and less than or equal to 4.0 mm, greater than or equal to 2.2 mm and less than or equal to 4.0 mm, greater than or equal to 2.3 mm and less than or equal to 4.0 mm, greater than or equal to 2.4 mm and less than or equal to 4.0 mm, greater than or equal to 2.5 mm and less than or equal to 3.8 mm). It has been found that such a relatively thin outer glass substrate can prevent impact events from negatively affecting optical performance by preventing impact-induced defects (such as cracks) from propagating outward from the plane of origin, thereby reducing the degree to which defects inhibit optical performance by reducing the scattering cross section of the defects. When propagating through thicker glass sheets, impact-induced cracks may distort out of plane, thereby increasing the reflectivity of the laminate and reducing the performance (e.g., transmission) of the window. The relatively thin outer glass substrate described herein can prevent such distortion and help maintain optical performance despite any impact-induced defects.

[0056] The relatively thick inner glass substrate described herein advantageously provides stiffness and avoids lamination-induced warping. When combined with an asymmetric structure (e.g., in terms of the thickness of the glass substrate on either side of the geometric center of the laminate cross-section), the glass-polymer laminates described herein have an asymmetric CTE-induced stress distribution. In embodiments, this asymmetric stress distribution may result in warping of the laminate (e.g., bending of the laminate due to different expansion and contraction of the layers). However, it has been found that maintaining the thickness of the inner glass substrate greater than 2.0 mm (e.g., greater than or equal to 2.1 mm, greater than or equal to 2.2 mm, greater than or equal to 2.3 mm, greater than or equal to 2.4 mm, greater than or equal to 2.5 mm, greater than or equal to 2.6 mm, greater than or equal to 2.7 mm, greater than or equal to 2.8 mm, greater than or equal to 2.9 mm, greater than or equal to 3.0 mm, greater than or equal to 2.5 mm and less than or equal to 3.8 mm) provides sufficient stiffness to prevent such warping, thereby enabling the glass substrate to maintain its original shape during and after lamination (e.g., the glass substrate can remain a planar sheet of glass throughout the lamination process to form a planar sensor window).

[0057] The relatively thick inner glass substrate of the glass-polymer laminates described herein can also help reduce the polymer layer bonded to the laminate (e.g., such that the polymer layer is only on one side of the inner glass substrate) by achieving an asymmetric laminate structure. Reducing the polymer layer can advantageously keep the optical transmittance of the laminate high throughout the sensing band to suit a particular sensor application. Thus, the relatively thick inner glass substrate described herein promotes the favorable optical properties of the glass-polymer laminate by controlling the shape of the laminate and reducing the need for polymer-based materials.

[0058] In various aspects, the glass-polymer laminates described herein may include multiple relatively thin outer glass substrates disposed on one side of a relatively thick inner glass substrate. In one example, a glass-polymer laminate according to the present disclosure may include an inner glass substrate, a first polymer layer disposed on the inner glass substrate, a first outer glass substrate disposed on the first polymer layer, a second polymer layer disposed on the first outer glass substrate, and a second outer glass substrate disposed on the second polymer layer. The additional outer glass substrates advantageously increase the thickness of glass that can be damaged with only minimal visibility (e.g., if an impact-induced crack propagates from the second outer glass substrate into the first outer glass substrate, the crack must also propagate through the first outer glass substrate before reaching the inner glass substrate and distorting out of plane to become more visible). In addition, such multiple outer glass substrate embodiments introduce additional layers of polymer material. As described herein, such layers can deform and attenuate impact energy, thereby making damage caused by impact less severe. Any number of outer glass substrates can be combined in the glass-polymer laminates described herein to provide the desired level of impact performance, but it is understood that additional polymer layers may reduce light transmission performance.

[0059] In an embodiment, the outer glass substrate is formed of an abnormal glass composition. Abnormal glass is a glass that tends to exhibit crack ring fracture behavior when the glass is subjected to a Vickers indenter test as described in the following documents: "Crack-resistant glass with high shear band density" by Gross et al., Journal of Non-Crystalline Solids, Volume 494 (2018), pages 13-20; and "Deformation and cracking behavior of glasses indented with diamond tips of various sharpness" by Gross, Journal of Non-Crystalline Solids, Volume 358 (2012), pages 3445-3452, both of which are incorporated in their entirety. Examples of abnormal glass can be borosilicate glass (such as the glass described in PCT patent application No. PCT / US2021 / 61966 filed on December 6, 2021, the entire text of which is hereby incorporated by reference, or Eagle Glass or 714AWF glass) or glasses with relatively high silica content. Such glasses tend to exhibit more favorable impact performance characteristics than glasses exhibiting normal fracture behavior, in which cracks extending radially from the indentation site tend to extend through the thickness of the glass, potentially leading to catastrophic failure. Unusual glasses, such as borosilicates, may also tend to exhibit relatively low CTEs, thereby limiting thermally induced damage from environmental exposure.

[0060] As used herein, the term "coefficient of thermal expansion" or CTE refers to a value obtained by measuring the expansion of a referenced material between 0°C and 300°C.

[0061] As used herein, the term "disposed" includes coating, depositing and / or forming a material onto a surface using any method known in the art. The disposed material may constitute a layer, as defined herein. The phrase "disposed on..." includes instances where the material is formed onto a surface such that the material is in direct contact with the surface, and also includes instances where the material is formed on the surface with one or more intervening materials between the disposed material and the surface. The intervening materials may constitute a layer, as defined herein.

[0062] In this article, ranges can be expressed as from "about" one specific value and / or to "about" another specific value. When such a range is expressed, another embodiment includes from the one specific value and / or to the other specific value (i.e., the range includes the endpoints clearly indicated). Similarly, when a value is expressed as an approximation by using the antecedent "about", it will be understood that the specific value forms another embodiment. For example, the range of "from about 1 to about 2" also clearly includes the range of "from 1 to 2". Similarly, the range of "about 1 to about 2" also clearly includes the range of "1 to 2". It will be further understood that the endpoints of each range are both significant with respect to the other endpoint and meaningful independently of the other endpoint.

[0063] Directional terms used herein (eg, up, down, right, left, front, back, top, bottom) are made with reference only to the drawings shown and are not intended to imply an absolute orientation.

[0064] Unless otherwise expressly stated, it is not intended that any method described herein be construed as requiring that its steps be performed in a particular order, nor is it intended that any apparatus be required to have a particular orientation. Thus, if a method claim does not actually recite an order to be followed by its steps, or any apparatus claim does not actually recite an order or orientation of individual components, or if there is no other specific indication in the claim or specification that the steps are to be subject to a particular order, or if a particular order or orientation of the components of the apparatus is not recited, then it is not intended that an order or orientation be inferred in any respect. This applies to any possible non-express basis for interpretation, including: matters of logic relating to the arrangement of steps, operational flow, order of components, or orientation of components; inferences from the ordinary meaning of grammatical organization or punctuation, and; the number or type of embodiments described in the specification.

[0065] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a" component includes aspects having two or more such components unless the context clearly dictates otherwise.

[0066] Reference now Figure 1 , the vehicle 10 includes one or more LiDAR systems 12. The one or more LiDAR systems 12 may be disposed anywhere on or in the vehicle 10. For example, the one or more LiDAR systems 12 may be disposed on a top 14 of the vehicle 10 and / or on a front 16 of the vehicle 10.

[0067] Reference now Figure 2Each of the one or more LiDAR systems 12 includes an electromagnetic radiation emitter and sensor 18 as is known in the art, which may be enclosed within a housing 20. The electromagnetic radiation emitter and sensor 18 emits emitted radiation 22 having a certain wavelength or range of wavelengths. The emitted radiation 22 exits the housing 20 through a window 24. If an object (not shown) in the external environment 26 is in the path of the emitted radiation 22, the emitted radiation 22 will be reflected from the object and return to the electromagnetic radiation emitter and sensor 18 as reflected radiation 28, initially incident on an outer surface 44 of the window. The outer surface 44 is a surface of the window 24 that is exposed to (or closest to) the external environment of the LiDAR system 12, such that the outer surface 44 is exposed to unconditioned conditions within the housing 20. After being incident on the outer surface 44, the reflected radiation 28 passes through the window 24 again to reach the electromagnetic radiation emitter and sensor 18. In an embodiment, the emitted radiation 22 and the reflected radiation 28 have a wavelength of 905 nanometers or 1550 nanometers, or have a bandwidth including 905 nanometers (e.g., from 880 nanometers to 930 nanometers) or 1550 nanometers (e.g., from 1525 nanometers to 1775 nanometers). Electromagnetic radiation other than the reflected radiation 28 (e.g., electromagnetic radiation having a wavelength within the visible spectrum) may or may not pass through the window 24, depending on the optical properties of the window 24 described herein. As used herein, the term "visible spectrum" is used to refer to the portion of the electromagnetic spectrum visible to the human eye, generally referring to electromagnetic radiation with a wavelength in the range of about 380 nanometers to 700 nanometers.

[0068] Reference now Figure 3 In an embodiment, the window 24 of each of the one or more LiDAR systems 12 may include a glass-polymer laminate 300. The glass-polymer laminate 300 includes a first surface 32 and an outer surface 44. The first surface 32 and the outer surface 44 are major surfaces of the glass-polymer laminate 300. In an embodiment, and with reference to Figure 2 , outer surface 44 is closest to external environment 26. First surface 32 is closest to electromagnetic radiation emitter and sensor 18. Emitted radiation 22 encounters first surface 32 before outer surface 44. Reflected radiation 28 encounters outer surface 44 before first surface 32.

[0069] In an embodiment, one or more of the first surface 32 and the outer surface 44 of the window may include one or more suitable surface treatments. For example, in an embodiment, at least one of the first surface 32 and the outer surface 44 includes an anti-reflective film. The anti-reflective film may be tailored to prevent reflection of the emitted radiation 22 and the reflected radiation 28. In an embodiment, the anti-reflective film includes a plurality of alternating layers of relatively low and high refractive index materials of suitable thickness to provide relatively low reflectivity and high transmittance in a particular wavelength range of interest. Any anti-reflective film described in International Patent Application No. PCT / US2020 / 35034 filed on May 29, 2020, International Patent Application No. PCT / US2020 / 35497 filed on June 1, 2020, U.S. Provisional Patent Application No. 63 / 284,161 filed on November 30, 2021, U.S. Provisional Patent Application No. 63 / 289,828 filed on December 15, 2021, and U.S. Provisional Patent Application No. 63 / 257,814 filed on October 20, 2021 (each of which is incorporated by reference in its entirety) may be used with the glass laminate 300. In an embodiment, one of the high refractive index layers of the anti-reflective film comprises a relatively high thickness of 1000 nanometers, so that when measured on one side of the anti-reflective film, the maximum hardness of the glass-polymer laminate 300 as measured by the Berkovich indenter hardness test is at least 8 GPa. Therefore, the construction of the anti-reflective film can improve the impact performance of the glass-polymer laminate 300.

[0070] Figure 3 The glass-polymer laminate 300 described in the drawings includes a first glass substrate 310, a second glass substrate 320, and a first polymer layer 315 disposed between the first glass substrate 310 and the second glass substrate 320. As shown in the figure, the first glass substrate 310 forms the outer surface 44 of the window 24 (see Figure 2 ). Thus, in the depicted example, the first glass substrate 310 forms an outer glass substrate, while the second glass substrate 320 forms an inner glass substrate.

[0071] The first glass substrate 310 may have a substantially different coefficient of thermal expansion (CTE) than the second glass substrate 320. For example, the first glass substrate 310 may have a low CTE, while the second glass substrate 320 exhibits a higher CTE than the first glass substrate 310. The first polymer layer 315 may include a UV-cured or heat-cured polymer. Curing the polymer at a temperature away from a predetermined use temperature (e.g., room temperature) results in a CTE difference between the glass substrates to create compressive stress on the first glass substrate 310 when the glass-polymer laminate 300 returns to the use temperature. The compressive stress on the first glass substrate 310 provides higher damage resistance and better scratch performance. Due to the ductile deformation of the first polymer layer 315, any cracks that do form in the first glass substrate 310 are arrested at the polymer interface (unlike brittle deformation at the interface in a molten laminate) and may not propagate into the second glass substrate 320, thereby reducing the visibility of the cracks and preventing catastrophic failure of the glass-polymer laminate 300.

[0072] Keeping the thickness of the first glass substrate 310 thin (e.g., having a thickness 50 of less than or equal to 300 μm) can help minimize the visibility of any cracks that form therein. Using a damage-resistant material such as a borosilicate, an alkaline earth aluminoborosilicate, or an alkali aluminoborosilicate for the first glass substrate 310 further improves impact performance over a monolithic ion-exchanged glass material, which is more susceptible to lateral cracking due to its large surface stress gradient.

[0073] In an embodiment, the material forming the first polymer layer 315 is selected to have stiffness at a relatively low thickness, thereby preventing the first glass substrate 310 and the second glass substrate 320 from flexing and breaking sharply. It has been found that polymers with relatively high elastic modulus, relatively high glass transition temperature, and relatively low ductile to brittle transition temperature can have a favorable effect on performance. In addition to various UV-curable and thermally curable polymers, thin film polymer laminates can also be used. Commercially available polymers (such as those described in International Patent Application No. PCT / US2021 / 60757 filed on November 24, 2021, the entire text of which is hereby incorporated by reference) can be used to form the polymer layer described herein.

[0074] Still reference Figure 3, the structure of the glass-polymer laminate 300 provides a number of advantages when compared to monolithic chemically strengthened or thermally strengthened glass-based articles, such as commercially available glass-based articles. The laminated structure provides comparable performance to chemically strengthened glass-based articles without the need for ion exchange treatment, thereby reducing the cost of the same performance level. In addition, the visibility of defects in the glass-based composite 300 is less objectionable over a wider range of impact events than a monolithic chemically strengthened glass-based article, thereby reducing the frequency of replacement during use. The glass-based composite 300 may also exhibit a degree of self-healing such that cracks that do form over time due to the compressive stresses in the first glass substrate 310 become less noticeable. From a manufacturing perspective, the glass-based composite 300 described herein may be cut from a "mother" sheet to the desired part size, even after the introduction of compressive stresses, which is difficult or impossible for a monolithic chemically strengthened glass-based article. The glass-based composite may also be considered repairable such that the application of a curable resin may reduce the appearance of cracks.

[0075] In an embodiment, the compressive stress in the first glass substrate 310 is caused by the mismatch in the coefficient of thermal expansion between the first glass substrate 310 and the second glass substrate 320. The material of the first polymer layer 315 is cured (e.g., heated to a curing temperature) at a temperature different from the expected use temperature (usually room temperature), and when the laminate is returned to the use temperature, the volume change of the second glass substrate 320 with a higher coefficient of thermal expansion (CTE) is greater than the volume change of the first glass substrate 310 with a lower CTE, which generates compressive stress in the first glass substrate 310.

[0076] In an embodiment, the greater the difference in CTE of the glasses of the first glass substrate 310 and the second glass substrate 320, and the greater the temperature difference between the curing temperature and the use temperature, the greater the compressive stress generated. In addition to the CTE of the glasses of the first glass substrate 310 and the second glass substrate 320, the glass relaxation behavior of the polymer forming the first polymer layer 315 also has a considerable influence on the final stress state in the glass-based composite product. The glass transition temperature, processing temperature, cooling rate, and elastic modulus of the polymer in the rubber state are important control parameters.

[0077] The first polymer layer 315 serves a variety of purposes. Perhaps most importantly, the first polymer layer 315 provides a mechanical bond between the first glass substrate 310 and the second glass substrate 320. During curing, the shrinkage of the first polymer layer 315 may impart additional compressive stress to the first glass substrate 310 and the second glass substrate 320 to which it is bonded, which is why the glass-polymer laminates described herein may exhibit slightly greater compressive stress than that simply due to the CTE mismatch between the first glass substrate 310 and the second glass substrate 320. This additional compression increases the damage resistance and strength of the glass-polymer laminate 300. In addition, the first polymer layer 315 also deflects and blocks any cracks that may propagate from one glass substrate to the other. Therefore, if the surface of the second glass substrate 320 is pristine and free of strength-limiting defects, it is expected to remain that way during use because it is protected by the first glass substrate 310 and the first polymer layer 315, which imparts great strength to the glass-polymer laminate 300 even if the first glass substrate 310 is compromised or damaged. To function in this manner, the ductile to brittle transition temperature of the polymer should be low, so that deformation of the first polymer layer 315 is purely elastic or elastic / plastic / viscoplastic over the operating temperature range (e.g., from -30°C to 50°C, from -10°C to 50°C, from 0°C to 30°C). Finally, the first polymer layer 315 helps to keep closed any cracks that do form in the glass substrate.

[0078] like Figure 3 As shown, the first glass substrate 310 includes a thickness 50 (which is measured, for example, between the outer surface 44 of the first glass substrate 310 and the second major surface 46). The first glass substrate 310 can be formed of a first glass composition and includes a first thermal expansion coefficient CTEG1. The second glass substrate 320 includes a thickness 52 (which is measured, for example, between the first surface 32 and the second major surface 36 of the second glass substrate 320). The second glass substrate 320 can be formed of a second glass composition and includes a second thermal expansion coefficient CTEG2. The first polymer layer 315 includes a thickness 56 and a thermal expansion coefficient CTEP1. In an embodiment, the difference between CTEG1 and CTEG2 is greater than or equal to 0.5 ppm / °C to promote strength-enhancing compressive stress to exist in the first glass substrate 310 after lamination.

[0079] The thickness 50 of the first glass substrate 310 is described as being less than the thickness 52 of the second glass substrate 320. In an embodiment, the thickness 50 is less than or equal to 20% of the thickness 52 (e.g., less than or equal to 19%, less than or equal to 18%, less than or equal to 17%, less than or equal to 16%, less than or equal to 15%, less than or equal to 14%, less than or equal to 13%, less than or equal to 12%, less than or equal to 11%, less than or equal to 10%, less than or equal to 9%, less than or equal to 8%, less than or equal to 7%, less than or equal to 6%, less than or equal to 5%, less than or equal to 4%, less than or equal to 3%). In an embodiment, the thickness 50 is less than or equal to 300 μm and greater than or equal to 10 μm (e.g., less than or equal to 250 μm, less than or equal to 200 μm, less than or equal to 190 μm, less than or equal to 180 μm, less than or equal to 170 μm, less than or equal to 160 μm, less than or equal to 150 μm, less than or equal to 140 μm, less than or equal to 130 μm, less than or equal to 120 μm, less than or equal to 110 μm, less than or equal to 100 μm, 90 μm or less), and the thickness 52 is greater than 2.0 mm (e.g., greater than or equal to 2.1 mm, greater than or equal to 2.2 mm, greater than or equal to 2.3 mm, greater than or equal to 2.4 mm, greater than or equal to 2.5 mm, greater than or equal to 2.6 mm, greater than or equal to 2.7 mm, greater than or equal to 2.8 mm, greater than or equal to 2.9 mm, greater than or equal to 3.0 mm, greater than or equal to 2.5 mm, and less than or equal to 3.8 mm). The relatively low thickness of the first glass substrate 310 can prevent cracking and twisting out of the plane, and cover more surface area in the direction perpendicular to the emitted radiation 22 (see Figure 2 ), thereby reducing the scattering cross section of damage to make any impact-induced damage on the outer surface 44 less noticeable. The relatively low thickness of the first glass substrate 310 can also enable the first glass substrate 310 to bend and dissipate impact energy, thereby reducing or preventing fracture. The relatively high thickness of the second glass substrate 320 increases the stiffness of the glass-polymer laminate 300 and prevents warping during the lamination process despite the asymmetric structure of the glass-polymer laminate 300.

[0080] In an embodiment, thickness 56 is less than thickness 52. In an embodiment, all polymer layers disposed between glass substrates in the glass-polymer laminates described herein may individually have a thickness of less than or equal to 150 μm. In an embodiment, thickness 56 is less than or equal to 150 μm, such as less than or equal to 145 μm, less than or equal to 140 μm, less than or equal to 135 μm, less than or equal to 130 μm, less than or equal to 125 μm, less than or equal to 120 μm, less than or equal to 115 μm, less than or equal to 110 μm, less than or equal to 105 μm, less than or equal to 100 μm, less than or equal to 95 μm, less than or equal to 90 μm, less than or equal to 85 μm, less than or equal to 80 μm, less than or equal to 75 μm. m, less than or equal to 70μm, less than or equal to 65μm, less than or equal to 60μm, less than or equal to 55μm, less than or equal to 50μm, less than or equal to 45μm, less than or equal to 40μm, less than or equal to 35μm, less than or equal to 30μm, less than or equal to 25μm, less than or equal to 20μm, less than or equal to 15μm, less than or equal to 10μm, less than or equal to 8μm, less than or equal to 6μm, less than or equal to 4μm, less than or equal to 2μm, less than or equal to 1μm, or less. In an embodiment, thickness 56 is greater than or equal to 1 μm and less than or equal to 150 μm, greater than or equal to 2 μm and less than or equal to 150 μm, for example, from greater than or equal to 4 μm and less than or equal to 145 μm, from greater than or equal to 6 μm and less than or equal to 140 μm, from greater than or equal to 8 μm and less than or equal to 135 μm, from greater than or equal to 10 μm and less than or equal to 130 μm, from greater than or equal to 15 μm and less than or equal to 125 μm, from greater than or equal to 20 μm and less than or equal to 120 μm, from greater than or equal to 25 μm and less than or equal to 115 μm, and from greater than or equal to 15 μm and less than or equal to 160 μm. From or equal to 30 μm to or less than 110 μm, from or equal to 35 μm to or less than 105 μm, from or equal to 40 μm to or less than 100 μm, from or equal to 45 μm to or less than 95 μm, from or equal to 50 μm to or less than 90 μm, from or equal to 55 μm to or less than 85 μm, from or equal to 60 μm to or less than 80 μm, from or equal to 65 μm to or less than 75 μm, from or equal to 2 μm to or less than 70 μm, and any and all subranges formed by these endpoints. In the case where multiple polymer layers are included in the glass-polymer laminate (e.g., as described herein), Figure 4), the polymer layer products may have different thicknesses. In other embodiments, where multiple polymer layers are included in the glass-polymer laminate, the polymer layers may have substantially equal or equal thicknesses. In embodiments, the polymer layer may be thinner than the glass substrate adjacent thereto. For example, in embodiments, thickness 56 is less than or equal to 75 μm (e.g., less than or equal to 50 μm, less than or equal to 25 μm), while thickness 50 is greater than 75 μm (e.g., greater than or equal to 100 μm, greater than or equal to 125 μm, greater than or equal to 150 μm).

[0081] Still reference Figure 3 , the glass-polymer laminate 300 includes a combined thickness 322 that represents a combination of thicknesses 50, 52, and 56. In an embodiment, the combined thickness 322 is less than or equal to 20 mm, such as less than or equal to 19 mm, less than or equal to 18 mm, less than or equal to 17 mm, less than or equal to 16 mm, less than or equal to 15 mm, less than or equal to 14 mm, less than or equal to 13 mm, less than or equal to 12 mm, less than or equal to 11 mm, less than or equal to 10 mm, less than or equal to 9 mm, less than or equal to 8 mm, less than or equal to 7 mm, less than or equal to 6 mm, less than or equal to 5 mm, less than or equal to 4 mm, less than or equal to 3 mm, less than or equal to 2 mm, less than or equal to 1.5 mm, less than or equal to 1 mm, or less. In an embodiment, the glass-based article has a thickness ranging from greater than or equal to 0.5 mm to less than or equal to 20 mm, for example, greater than or equal to 1 mm to less than or equal to 19 mm, greater than or equal to 2 mm to less than or equal to 18 mm, greater than or equal to 3 mm to less than or equal to 17 mm, greater than or equal to 4 mm to less than or equal to 16 mm, greater than or equal to 5 mm to less than or equal to 15 mm, greater than or equal to 6 mm to less than or equal to 14 mm, greater than or equal to 7 mm to less than or equal to 13 mm, greater than or equal to 8 mm to less than or equal to 12 mm, greater than or equal to 9 mm to less than or equal to 11 mm, greater than or equal to 0.5 mm to less than or equal to 10 mm, and any and all sub-ranges formed by these endpoints.

[0082] As described herein, the first glass substrate layer 310 and the second glass substrate layer 320 have a coefficient of thermal expansion (CTE) mismatch. The CTE difference between the first glass substrate layer 310 and the second glass substrate layer 320 is greater than 0.5 ppm / °C, such that |CTEG1 - CTEG2| > 0.5 ppm / °C. In an embodiment, |CTEG1 - CTEG2| > 1 ppm / °C. Generally, the greater the CTE mismatch of the glass substrate layer, the greater the compressive stress generated. In an embodiment, CTEG1 < CTEG2. In other embodiments, CTEG1 > CTEG2. The glass substrate layer with the higher CTE determines whether the curing of the polymer layer occurs above or below the use temperature in order to generate compressive stress in the first glass substrate layer 310. In an embodiment, when CTEG1 < CTEG2, the curing temperature is greater than the use temperature. In an embodiment, when CTEG1 > CTEG2, the curing temperature is lower than the use temperature.

[0083] The relationship between the CTE of the first polymer layer 315 and the average CTE of the first glass substrate layer 310 and the second glass substrate layer 320 can also be considered. In an embodiment, CTEP1 - (CTEG1 + CTEG2) / 2 > 1 ppm / °C.

[0084] The first glass substrate 310 includes a certain compressive stress. The compressive stress improves the fracture resistance of the glass-polymer laminate 300 and reduces the propagation of cracks. In an embodiment, the compressive stress of the first glass substrate 310 is greater than or equal to 5 MPa, such as greater than or equal to 10 MPa, greater than or equal to 15 MPa, greater than or equal to 20 MPa, greater than or equal to 25 MPa, greater than or equal to 30 MPa, greater than or equal to 35 MPa, greater than or equal to 40 MPa, greater than or equal to 45 MPa, greater than or equal to 50 MPa, greater than or equal to 55 MPa, greater than or equal to 60 MPa, greater than or equal to 65 MPa, greater than or equal to 70 MPa, greater than or equal to 75 MPa, greater than or equal to 80 MPa, greater than or equal to 85 MPa, greater than or equal to 90 MPa, greater than or equal to 95 MPa, greater than or equal to 100 MPa, or greater. In an embodiment, the compressive stress of the first glass substrate 310 is from greater than or equal to 5 MPa to less than or equal to 100 MPa, for example, greater than or equal to 10 MPa to less than or equal to 95 MPa, greater than or equal to 15 MPa to less than or equal to 90 MPa, greater than or equal to 20 MPa to less than or equal to 85 MPa, greater than or equal to 25 MPa to less than or equal to 80 MPa, greater than or equal to 30 MPa to less than or equal to 75 MPa, greater than or equal to 35 MPa to less than or equal to 70 MPa, greater than or equal to 40 MPa to less than or equal to 65 MPa, greater than or equal to 45 MPa to less than or equal to 60 MPa, greater than or equal to 50 MPa to less than or equal to 55 MPa, and any and all sub-ranges formed by these endpoints.

[0085] In an embodiment, the compressive stress of the first glass substrate 310 is greater than or equal to 5 MPa and less than or equal to 40 MPa. It has been found that maintaining the compressive stress within this range is advantageous because the tensile stress in the second glass substrate 320 is maintained at a level less than or equal to 10 MPa (e.g., less than or equal to 9.5 MPa, less than or equal to 9.0 MPa, less than or equal to 8.5 MPa, less than or equal to 8.0 MPa, less than or equal to 7.5 MPa). Higher tensile stress levels in the second glass substrate 320 may increase the risk of catastrophic failure of the glass-polymer laminate 300 in response to a particularly severe impact event because such tensile stresses have a tendency to propagate defects.

[0086] In an embodiment, the first glass substrate 310 may include a substantially uniform compressive stress. In an embodiment, the first glass substrate 310 includes an average compressive stress, and the variation of the compressive stress across the thickness of the first glass substrate 310 is less than 20% of the average compressive stress. In such an embodiment, the average compressive stress of the first glass substrate 310 may be any of the above-mentioned compressive stress values, such as greater than or equal to 5 MPa, greater than or equal to 10 MPa, and so on.

[0087] The first glass substrate 310 can be characterized by an exposed surface compressive stress at the outer surface 44. The outer surface 44 is not in contact with the first polymer layer 315, and therefore may be contacted during an impact event, and therefore is most likely to suffer damage during normal use. In an embodiment, the exposed surface of the first glass substrate 310 has a compressive stress, which can be any of the above-mentioned compressive stress values, such as greater than or equal to 5 MPa, greater than or equal to 10 MPa, and so on.

[0088] The first glass substrate 310 can be characterized by a bonding surface compressive stress at the second major surface 46 in contact with the first polymer layer 315. In embodiments, the bonding surface of the first glass substrate 310 has a compressive stress, which can be any of the above-mentioned compressive stress values, such as greater than or equal to 5 MPa, greater than or equal to 10 MPa, etc. In embodiments where the compressive stress in the first glass substrate 310 is substantially uniform, the compressive stress at the outer surface 44 can be substantially equal to the compressive stress at the second major surface 46.

[0089] In an embodiment, the first glass substrate 310 and the second glass substrate 320 are not thermally or chemically strengthened. That is, the first glass composition and the second glass composition used to form the first glass substrate 310 and the second glass substrate 320 are not strengthened by immersion in a molten salt bath or subjected to a thermal tempering heat treatment to form a compressive stress that is not caused by a CTE mismatch between the first glass composition and the second glass composition. Such an embodiment can advantageously eliminate processing steps and save costs.

[0090] Embodiments are also contemplated in which the first glass substrate 310 and / or the second glass substrate 320 are formed of a chemically strengthened glass-based material. The chemically strengthened glass-based material includes a stress curve that is additively combined with the compressive stress generated by the CTE mismatch of the glass substrates, resulting in a maximum compressive stress in the first glass substrate 310 or the second glass substrate 320 that may be significantly higher than the compressive stress caused by the CTE mismatch alone. In such embodiments, the compressive stress of the first glass substrate 310 and / or the second glass substrate 320 may be greater than or equal to 200 MPa, for example, greater than or equal to 250 MPa, greater than or equal to 300 MPa, greater than or equal to 350 MPa, greater than or equal to 400 MPa, greater than or equal to 450 MPa, greater than or equal to 500 MPa, greater than or equal to 550 MPa, greater than or equal to 600 MPa, greater than or equal to 650 MPa, greater than or equal to 700 MPa, greater than or equal to 750 MPa, greater than or equal to 800 MPa, greater than or equal to 850 MPa, greater than or equal to 900 MPa, greater than or equal to 950 MPa, or greater. In an embodiment, the compressive stress of the first glass substrate 310 is from greater than or equal to 200 MPa to less than or equal to 1000 MPa, for example, greater than or equal to 250 MPa to less than or equal to 950 MPa, greater than or equal to 300 MPa to less than or equal to 900 MPa, greater than or equal to 350 MPa to less than or equal to 850 MPa, greater than or equal to 400 MPa to less than or equal to 800 MPa, greater than or equal to 450 MPa to less than or equal to 750 MPa, greater than or equal to 500 MPa to less than or equal to 700 MPa, greater than or equal to 550 MPa to less than or equal to 650 MPa, greater than or equal to 200 MPa to less than or equal to 600 MPa, and any and all sub-ranges formed by these endpoints.

[0091] The second glass substrate 320 may be characterized by a Young's modulus. In an embodiment, the Young's modulus EG2 of the second glass substrate 320 may be greater than or equal to 5 GPa, such as greater than or equal to 10 GPa, greater than or equal to 15 GPa, greater than or equal to 20 GPa, greater than or equal to 25 GPa, greater than or equal to 30 GPa, greater than or equal to 35 GPa, greater than or equal to 40 GPa, greater than or equal to 45 GPa, greater than or equal to 50 GPa, greater than or equal to 55 GPa, greater than or equal to 60 GPa, greater than or equal to 65 GPa, greater than or equal to 70 GPa, greater than or equal to 75 GPa, or greater. In an embodiment, EG2 is from greater than or equal to 5 GPa to less than or equal to 80 GPa, such as greater than or equal to 10 GPa to less than or equal to 75 GPa, greater than or equal to 15 GPa to less than or equal to 70 GPa, greater than or equal to 20 GPa to less than or equal to 65 GPa, greater than or equal to 25 GPa to less than or equal to 60 GPa, greater than or equal to 30 GPa to less than or equal to 55 GPa, greater than or equal to 35 GPa to less than or equal to 50 GPa, greater than or equal to 40 GPa to less than or equal to 45 GPa, and any and all subranges formed by these endpoints. Unless otherwise indicated, the Young's modulus of the glass substrate is measured by resonant ultrasonic spectroscopy of the general type set forth in ASTM E2001-13, entitled "Standard Guide for Resonant Ultrasound Spectroscopy for Defect Detection in Both Metallic and Non-metallic Parts".

[0092] The Young's modulus EG2 of the second glass substrate 320 can be described relative to the Young's modulus TP1 of the first polymer layer. In an embodiment, the Young's modulus of the second glass substrate 320 is greater than the Young's modulus of the first polymer layer, such that EG2>EP1.

[0093] The glass substrate may include glass or glass ceramic material. In an embodiment, the first glass substrate 310 and the second glass substrate 320 may have different compositions. In an embodiment, the second glass substrate 320 is formed of aluminosilicate glass, such as aluminosilicate glass, aluminoborosilicate glass, soda-lime glass. In an embodiment, the first glass substrate 310 is borosilicate glass, aluminoborosilicate glass, such as alkali-free aluminoborosilicate glass.

[0094] The first glass substrate 310 and the second glass substrate 320 may be selected to provide desired optical properties. In an embodiment, the glass substrate has a transmittance greater than or equal to 90% in the wavelength range of interest. The wavelength range of interest may vary depending on the application. For example, when used as the window 24 of the LiDAR system 12 (see Figure 2 ), the wavelength range of interest may include 905 nanometers or 1550 nanometers. In embodiments, the wavelength range of interest includes a center wavelength of 905 nanometers or 1550 nanometers, and a wavelength range around the center wavelength (e.g., + / - 10 nanometers, + / - 20 nanometers, + / - 30 nanometers, + / - 40 nanometers, + / - 50 nanometers, + / - 100 nanometers). In embodiments, for example, for applications other than the LiDAR system 12, such as a camera cover lens, the wavelength range of interest may be the visible spectrum, or from 380 nanometers to 700 nanometers. In embodiments, the light transmittance may be greater than or equal to 91%, greater than or equal to 92%, greater than or equal to 93%, greater than or equal to 94%, greater than or equal to 95%, greater than or equal to 96%, greater than or equal to 97%, greater than or equal to 98%, greater than or equal to 99%, or greater throughout the wavelength range of interest. Unless otherwise indicated, transmittance is measured according to ASTM D1003 using illuminant C with a Haze-gard Transparency Transmission Haze Meter.

[0095] In an embodiment, at least one of the first glass substrate 310 and the second glass substrate 320 may have a composition including about 50 mol% to about 85 mol% SiO2, about 5 mol% to about 30 mol% Al2O3, and about 5 mol% to about 30 mol% B2O3. The glass substrate may include a glass composition produced according to U.S. Pat. No. 7,851,394 and / or U.S. Pat. No. 7,534,734, each of which is incorporated herein by reference in its entirety.

[0096] In an embodiment, at least one of the first glass substrate 310 and the second glass substrate 320 may have an alkali-aluminosilicate composition, such as those compositions commonly subjected to ion exchange strengthening processes and used in mobile electronic devices. Alkali-aluminosilicate glass can be used in glass-based articles in ion-exchanged or non-ion-exchanged forms. In an embodiment, the alkali-aluminosilicate glass substrate may be substantially free of or free of lithium. The glass substrate may include a glass composition according to U.S. Patent Application Publication No. 2013 / 0122284A1, published on May 16, 2013, which is incorporated herein by reference in its entirety.

[0097] In an embodiment, the first glass substrate 310 is formed of a glass composition that exhibits abnormal fracture behavior. Examples of abnormal glass can be borosilicate glass (such as the glass described in PCT patent application No. PCT / US2021 / 61966 filed on December 6, 2021, which is hereby incorporated by reference in its entirety) and Eagle manufactured by Corning Incorporated. or 714AWF glass. Such glasses tend to exhibit more favorable impact performance characteristics than glasses exhibiting normal fracture behavior, in which cracks extending radially from the indentation site tend to extend through the thickness of the glass, potentially leading to catastrophic failure. Unusual glasses, such as borosilicate, may also tend to exhibit relatively low CTEs, thereby limiting thermally induced damage from environmental exposure.

[0098] The first polymer layer 315 may be formed of any suitable polymer material. In an embodiment, the first polymer layer 315 may include a resin, such as an optically clear resin, such as a commercially available resin commonly used to repair windshields. In an embodiment, the first polymer layer 315 may include a UV curable resin or a thermally curable resin. In an embodiment, the first polymer layer 315 may include an epoxy resin or an acrylate. In an embodiment, the first polymer layer 315 may also include a photoinitiator to provide the desired curing behavior. In the case of including multiple polymer layers (as described herein), Figure 4 The polymer layers may be formed of the same material or different materials. It should be generally understood that any property described herein with reference to the first polymer layer may also be attributed to any other polymer layer included in the glass-based article.

[0099] The material used to form the first polymer layer 315 (and any other polymer layers present) can be characterized based on the glass transition temperature. The glass transition temperature affects the compressive stress generated due to the CTE mismatch between the first glass substrate 310 and the second glass substrate 320. In an embodiment, the glass transition temperature TgP1 of the first polymer layer 315 is greater than or equal to 20°C, such as greater than or equal to 30°C, greater than or equal to 40°C, greater than or equal to 50°C, greater than or equal to 60°C, greater than or equal to 70°C, greater than or equal to 80°C, greater than or equal to 90°C, greater than or equal to 100°C, greater than or equal to 110°C, greater than or equal to 120°C, greater than or equal to 130°C, greater than or equal to 140°C, greater than or equal to 150°C, or greater. In an embodiment, the glass transition temperature TgP1 of the first polymer layer 315 is from greater than or equal to 20°C to less than or equal to 200°C, for example, greater than or equal to 30°C to less than or equal to 190°C, greater than or equal to 40°C to less than or equal to 180°C, greater than or equal to 50°C to less than or equal to 170°C, greater than or equal to 60°C to less than or equal to 160°C, greater than or equal to 70°C to less than or equal to 150°C, greater than or equal to 80°C to less than or equal to 140°C, greater than or equal to 90°C to less than or equal to 130°C, greater than or equal to 100°C to less than or equal to 120°C, greater than or equal to 20°C to less than or equal to 110°C, and any and all subranges formed by these endpoints. Unless otherwise indicated, the glass transition temperature of the polymer is measured by dynamic mechanical analysis.

[0100] The first polymer layer 315 can also be characterized based on the storage modulus. In an embodiment, the storage modulus of the first polymer layer at a temperature between 0° C. and 40° C. is greater than or equal to 5 MPa and less than or equal to 20,000 MPa, such as greater than or equal to 2,000 MPa and less than or equal to 5,000 MPa, and any and all subranges formed by these endpoints.

[0101] In an embodiment, the first polymer layer 315 does not exhibit brittle deformation behavior at 20° C. In other words, the first polymer layer 315 may exhibit ductile deformation behavior at 20° C. The non-brittle deformation behavior of the first polymer layer 315 may prevent cracks from extending from one glass substrate through the polymer layer to another glass substrate, which is also referred to as arresting cracks.

[0102] The first polymer layer 315 may have optical properties compatible with the first glass substrate 310 and the second glass substrate 320. In an embodiment, as described herein, the first polymer layer 315 may have a transmittance greater than or equal to 90% in the wavelength range of interest. In an embodiment, the material constituting the first polymer layer 315 is selected to have a post-curing refractive index np1 measured at 550 nanometers. In an embodiment, np1 is selected to substantially match the refractive index ng1 of the first glass substrate 310 measured at 550 nanometers and / or the refractive index ng2 of the second glass substrate 320 measured at 550 nanometers. In an embodiment, at 550 nanometers, np1-ng1 is less than or equal to 0.3 (e.g., less than or equal to 0.2, less than or equal to 0.1). In an embodiment, np1-ng2 is less than or equal to 0.3 (e.g., less than or equal to 0.2, less than or equal to 0.1). In an embodiment, np1 is preferably selected to be within 0.1 of ng1. Such index matching can make any impact-induced defects in the first glass substrate 310 difficult to see by avoiding reflections caused by the refractive index contrast at the interface between the first glass layer 310 and the first polymer layer 315. However, when the first polymer layer 315 is relatively thin (e.g., less than or equal to 75 μm), such index matching may not be required to reduce the visibility of defects.

[0103] The first polymer layer 315 can be relatively stiff, such as a polymer having an elastic modulus greater than or equal to 100 MPa at a strain rate of 1 / s. The stiffness of the first polymer layer 315 can constrain the glass substrate, thereby preventing the growth of cracks in the glass substrate and preventing the glass substrate from flexing and breaking. The first polymer layer 315 can have an elastic modulus greater than or equal to 100 MPa at a strain rate of 1 / s, such as greater than or equal to 105 MPa, greater than or equal to 110 MPa, greater than or equal to 115 MPa, greater than or equal to 120 MPa, greater than or equal to 125 MPa, or greater. In an embodiment, the stiffness of the polymer layer may be related to the thickness of the polymer layer such that the elastic modulus of the polymer layer divided by the thickness of the polymer layer is greater than or equal to 1 MPa / μm, such as greater than or equal to 2 MPa / μm, greater than or equal to 3 MPa / μm, greater than or equal to 4 MPa / μm, greater than or equal to 5 MPa / μm, greater than or equal to 6 MPa / μm, greater than or equal to 7 MPa / μm, greater than or equal to 8 MPa / μm, greater than or equal to 9 MPa / μm, greater than or equal to 10 MPa / μm, or greater. Unless otherwise indicated, the elastic modulus of the polymer is measured by dynamic mechanical analysis.

[0104] The first polymer layer 315 may also be fracture resistant. In an embodiment, the fracture toughness of the polymer layer is greater than or equal to 0.8 MPa√m, such as greater than or equal to 0.81 MPa√m, greater than or equal to 0.82 MPa√m, greater than or equal to 0.83 MPa√m, greater than or equal to 0.84 MPa√m, greater than or equal to 0.85 MPa√m, or greater.

[0105] The first polymer layer 315 may also be characterized based on a change in volume as a function of temperature. This phenomenon is often referred to as shrinkage. The polymer may also exhibit shrinkage due to the curing process. In an embodiment, the polymer undergoes a shrinkage greater than or equal to 1%, such as greater than or equal to 2%, greater than or equal to 3%, or greater during the curing process.

[0106] In an embodiment, the first polymer layer 315 may include one or more additives to modify its properties. In an embodiment, the polymer layer may include carbon nanotubes, such as multi-walled carbon nanotubes. The addition of carbon nanotubes to the polymer layer may increase the fracture resistance of the glass-based article, as shown, for example, by a drop ball test. Without being bound by any particular theory, the addition of carbon nanotubes to the polymer may increase the storage modulus, Young's modulus, and tensile strength of the polymer layer, resulting in improved crack resistance. In an embodiment, the polymer layer may include carbon nanotubes in an amount of about 1%.

[0107] In an embodiment, the first polymer layer 315 includes one or more colorants. The addition of colorants to the first polymer layer 315 can provide a pleasing aesthetic appearance to the glass-based article as a whole without degrading its mechanical properties. In an embodiment, the polymer layer can include a colorant in an amount greater than or equal to 0.1 weight percent to less than or equal to 30 weight percent. The colorant can be selected to be compatible with the composition of the polymer layer. For example, when the polymer layer is an epoxy resin, an epoxy-based colorant can be used. For example, in the case of an epoxy resin adhesive, one can dope 0.1-30 weight percent of an epoxy-based colorant in the epoxy resin precursor mixture, such as the colorants from Specialty Polymers & Services, Inc. series. Likewise, Orcozinedyes and OrcoTint NS dyes from Orco (Organic Dyes and Pigments) can also be used for acrylate-based adhesives. A suitable pigment dispersion (which includes, for example, a suitable pigment and a monomer) can be combined in the material used to form the first polymer layer 315.

[0108] In an embodiment, the glass-polymer laminate 300 may appear transparent and colorless. In an embodiment, the transmittance of the glass-polymer laminate 300 may be greater than or equal to 90% in the wavelength range of 400 nanometers to 750 nanometers, such as greater than or equal to 91%, greater than or equal to 92%, greater than or equal to 93%, greater than or equal to 94%, greater than or equal to 95%, greater than or equal to 96%, greater than or equal to 97%, greater than or equal to 98%, greater than or equal to 99%, or greater.

[0109] The glass-polymer laminate 300 article may have any suitable geometry. In an embodiment, the glass-polymer laminate 300 is substantially flat or planar. In some embodiments, the glass-polymer laminate 300 may include an opening or recess, such as an opening for accommodating a camera, a speaker, a microphone, or a fingerprint sensor.

[0110] The glass-polymer laminates described herein may be produced by any suitable lamination process. Generally, glass-based laminates are produced by disposing a polymer layer between glass substrates and then curing the polymer layer in an environment at a temperature different from the expected use temperature. In the event that more than two glass substrates are to be included in the glass-based article, the disposing steps may be repeated for each additional glass substrate to be added to form a laminated stack. In embodiments where more than one polymer layer is present, all polymer layers may be cured simultaneously.

[0111] After lamination and curing of the polymer layers, the glass-based article can be cut or machined into the desired geometry. This enables large sheets of the glass-based article to be formed and subsequently cut into the desired part sizes, thereby increasing manufacturing efficiency and flexibility. After the glass-based article is cut into the desired part size, an edge finishing process can be used to reduce the total number of defects in the cut edge and produce an edge profile that is less susceptible to failure when the glass-based article is subjected to bending stresses. In an embodiment, the glass substrate can be cut and machined into the desired final geometry prior to assembly and curing of the laminate stack.

[0112] The polymer layer can be provided by any method capable of producing a polymer layer having a desired thickness. In an embodiment, the polymer layer can be provided using a scraper, a roller, a spray system, or any other technique known in the art. In an embodiment, the polymer layer is provided using a flexographic or gravure printing technique. Selecting an appropriate setting technique enables the thickness of the polymer layer to be uniformly controlled. In an embodiment, a polymer layer having a thickness variation of less than or equal to 3 μm is produced using flexographic or gravure printing techniques. The polymer layer can be formed by a liquid adhesive composition. In an embodiment, the polymer layer can be deposited as a preformed film. After the polymer layer is provided between the glass substrates, pressure can be applied to the glass substrates to remove any bubbles or excess polymer from the laminate.

[0113] The curing of the polymer layer occurs in an environment at a curing temperature TC, where the curing temperature is different from the expected use temperature (e.g., room temperature). After the polymer layer is cured, the glass-based article is returned to the expected use temperature, and the CTE difference between the glass substrates generates compressive stress in the glass-based article (e.g., in the first glass substrate 310). In an embodiment, the difference between TC and room temperature (|TC-20°C|) is greater than or equal to 10°C, such as greater than or equal to 15°C, greater than or equal to 20°C, greater than or equal to 25°C, greater than or equal to 30°C, greater than or equal to 35°C, greater than or equal to 40°C, greater than or equal to 45°C, greater than or equal to 50°C, greater than or equal to 55°C, greater than or equal to 60°C, greater than or equal to 65°C, greater than or equal to 70°C, greater than or equal to 75°C, greater than or equal to 80°C, greater than or equal to 85°C, greater than or equal to 90°C, greater than or equal to 95°C, greater than or equal to 100°C, greater than or equal to 105°C, greater than or equal to 110°C, greater than or equal to 115°C, greater than or equal to 120°C, or greater. Prior to curing the polymer, the laminate may be kept in a curing temperature environment for a period of time, which may be referred to as preheating. This allows the laminate to substantially equilibrate to the curing temperature. In embodiments, the laminate can be maintained in a curing temperature environment for greater than or equal to 2 minutes, such as greater than or equal to 3 minutes, greater than or equal to 4 minutes, greater than or equal to 5 minutes, greater than or equal to 6 minutes, greater than or equal to 7 minutes, greater than or equal to 8 minutes, greater than or equal to 9 minutes, greater than or equal to 10 minutes, or longer.

[0114] In an embodiment, the polymer layer can be cured by irradiating the polymer layer with ultraviolet radiation. In an embodiment, the polymer layer can be cured by heat treating the polymer layer, for example, by heating the entire laminate or locally heating the polymer layer. For example, the laminate can be placed in an oven, in a furnace, or on a hot plate to heat treat and cure the polymer layer. In some embodiments, a combination of ultraviolet radiation and heat treatment can be used to cure the polymer layer. The ultraviolet irradiation used to cure the polymer layer can be sustained for any time period sufficient to produce the desired level of cure. In an embodiment, the duration of the ultraviolet irradiation is greater than or equal to 0.5 minutes, such as greater than or equal to 1 minute, greater than or equal to 2 minutes, greater than or equal to 3 minutes, greater than or equal to 4 minutes, greater than or equal to 5 minutes, greater than or equal to 6 minutes, greater than or equal to 7 minutes, greater than or equal to 8 minutes, greater than or equal to 9 minutes, greater than or equal to 10 minutes, or longer. Curing can be carried out in any environment capable of maintaining the desired curing temperature and accommodating the glass-based product. In an embodiment, curing is carried out in an oven, a furnace, a refrigerator, a freezer, or other environmental chambers.

[0115] The curing temperature may be higher or lower than the expected use temperature, and the relative CTE value of the glass substrate is selected accordingly to generate compressive stress in the exposed glass substrate (such as the first glass substrate 310). In an embodiment, TC is greater than or equal to 30°C (e.g., greater than or equal to 50°C), and CTEG2>CTEG1. In an embodiment, TC is less than or equal to 0°C, and CTEG1>CTEG2. The curing temperature may also be selected based on the glass transition temperature of the polymer layer. In an embodiment, the curing temperature is greater than the glass transition temperature of the polymer layer by more than 10°C (TC≥TgP1+10°C).

[0116] The glass-based article may be subjected to additional UV exposure after returning to a use temperature (e.g., room temperature). The additional UV exposure ensures that the polymer layer is fully cured. In an embodiment, the duration of the additional UV exposure is greater than or equal to 1 minute, such as greater than or equal to 2 minutes, greater than or equal to 3 minutes, greater than or equal to 4 minutes, greater than or equal to 5 minutes, greater than or equal to 6 minutes, greater than or equal to 7 minutes, greater than or equal to 8 minutes, greater than or equal to 9 minutes, greater than or equal to 10 minutes, or longer.

[0117] The process of producing the glass-based article may include a heat treatment step after curing the polymer layer. In an embodiment, after the polymer layer is cured, the glass-based article is heated to a temperature greater than or equal to 40° C. This additional heat treatment may help further cure the polymer layer.

[0118] Figure 4A glass-polymer laminate 400 is schematically depicted according to an example embodiment. In an embodiment, the glass-polymer laminate 400 may be used as the window 24 of the LiDAR system 12 (see FIG. Figure 2 ). Glass-polymer laminate 400 is depicted as including first glass substrate 410, first polymer layer 415, second glass substrate 420, second polymer layer 425, and third glass substrate 430. Figure 4 As shown, the first glass substrate 410 includes a thickness 412, the second glass substrate 420 includes a thickness 422, and the third glass substrate 430 includes a thickness 432. In an embodiment, the first glass substrate 410 and the second glass substrate 420 are outer glass substrates, so that the outer surface 44 (see FIG. Figure 2 ) is formed by first glass substrate 410, and third glass substrate 430 is an inner glass substrate. Therefore, thickness 432 can be significantly greater than thicknesses 412 and 422. In an embodiment, first glass substrate 410 and second glass substrate 420 are constructed in a manner (e.g., in terms of thickness and glass composition) similar to that described herein. Figure 3 The first glass substrate 310 of the glass-polymer laminate 300 described above is similar. In an embodiment, the third glass substrate 430 is constructed in the same manner (e.g., in terms of thickness and glass composition) as described herein. Figure 3 The second glass substrate 320 is described similarly.

[0119] In an embodiment, thicknesses 412 and 422 (individually) are less than or equal to 20% of thickness 432 (e.g., less than or equal to 19%, less than or equal to 18%, less than or equal to 17%, less than or equal to 16%, less than or equal to 15%, less than or equal to 14%, less than or equal to 13%, less than or equal to 12%, less than or equal to 11%, less than or equal to 10%, less than or equal to 9%, less than or equal to 8%, less than or equal to 7%, less than or equal to 6%, less than or equal to 5%, less than or equal to 4%, less than or equal to 3%). In an embodiment, thicknesses 412 and 422 are less than or equal to 300 μm (e.g., less than or equal to 200 μm, less than or equal to 175 μm, less than or equal to 150 μm, less than or equal to 125 μm, less than or equal to 100 μm, greater than or equal to 10 μm and less than or equal to 200 μm), while thickness 432 is greater than 2.0 mm (e.g., greater than or equal to 2.1 mm, greater than or equal to 2.2 mm, greater than or equal to 2.3 mm, greater than or equal to 2.4 mm, greater than or equal to 2.5 mm, greater than or equal to 2.6 mm, greater than or equal to 2.7 mm, greater than or equal to 2.8 mm, greater than or equal to 2.9 mm, greater than or equal to 3.0 mm, all less than 3.8 mm). Such a combination of thicknesses helps reduce the adverse effects of impact-induced defects on optical performance while providing sufficient stiffness to prevent significant warping during the lamination process.

[0120] In an embodiment, the first glass substrate 410 and the second glass substrate 420 are composed of a glass having a different (e.g., lower) CTE than the third glass substrate 430, such that after being subjected to the curing temperature described herein, both the first glass substrate 410 and the second glass substrate 420 have compressive stresses therein. As described herein, embodiments are contemplated in which the first glass substrate 410 and the second glass substrate 420 include the same thickness and composition. Embodiments are also contemplated in which the first glass substrate 410 and the second glass substrate 420 differ from each other in at least one of thickness and composition.

[0121] The construction of the first polymer layer 415 and the second polymer layer 425 can be similar to that described herein. Figure 3The first polymer layer 315 of the glass-polymer laminate 300 is shown. As shown, the first polymer layer 415 includes a thickness 416 and the second polymer layer includes a thickness 416. In an embodiment, both thicknesses 416 and 426 (individually) are greater than or equal to 1 μm and less than or equal to 150 μm, such as from greater than or equal to 4 μm to less than or equal to 145 μm, from greater than or equal to 6 μm to less than or equal to 140 μm, from greater than or equal to 8 μm to less than or equal to 135 μm, from greater than or equal to 10 μm to less than or equal to 130 μm, from greater than or equal to 15 μm to less than or equal to 125 μm, from greater than or equal to 20 μm to less than or equal to 120 μm, from greater than or equal to 25 μm to less than or equal to 115 μm, from greater than or equal to 30 um to less than or equal to 110um, from greater than or equal to 35um to less than or equal to 105um, from greater than or equal to 40um to less than or equal to 100um, from greater than or equal to 45um to less than or equal to 95um, from greater than or equal to 50um to less than or equal to 90um, from greater than or equal to 55um to less than or equal to 85um, from greater than or equal to 60um to less than or equal to 80um, from greater than or equal to 65um to less than or equal to 75um, from greater than or equal to 2um to less than or equal to 70um, and any and all subranges formed by these endpoints. As described herein, embodiments are contemplated in which the first polymer layer 415 and the second polymer layer 425 include the same thickness and composition. Embodiments are also contemplated in which the first polymer layer 415 and the second polymer layer 425 differ from each other in at least one of thickness and composition.

[0122] In an embodiment, the combined thickness of the first glass substrate 410 and the second glass substrate 420 (i.e., the combined outer layer thickness of the relatively thin outer glass substrates of the glass-polymer laminate 400) is less than or equal to 300 μm (e.g., less than or equal to 300 μm and greater than or equal to 15 μm, less than or equal to 300 μm and greater than or equal to 30 μm, less than or equal to 300 μm and greater than or equal to 50 μm, less than or equal to 300 μm and greater than or equal to 30 μm, less than or equal to 300 μm and greater than or equal to 100 μm, less than or equal to 300 μm and greater than or equal to 200 μm). Such a combined outer layer thickness is advantageous for each of the first glass substrate 410 and the second glass substrate 420 to be thin enough to prevent defects from distorting out of plane and becoming more apparent, while still being thick enough to prevent impact-induced defects from reaching the third glass substrate 430, which, as described herein, may be under tensile stresses that tend to magnify defects.

[0123] As described herein, the glass-polymer laminate 400 may be formed by creating a stack of a first glass substrate 410, a second glass substrate 420, and a third glass substrate 430 with uncured versions of the first polymer layer 415 and the second polymer layer 425 disposed therebetween. After being heated to a curing temperature outside of the use temperature range described herein at which the polymer materials of the first polymer layer 415 and the second polymer layer 425 are cured, the stack is then heated or cooled to the use temperature range in which differential volumetric shrinkage occurs and the bonding of the first glass substrate 410 and the second glass substrate 420 to the third glass substrate 430 via the first polymer layer 415 and the second polymer layer 425 results in compressive stress in each of the first glass substrate 410 and the second glass substrate 420. In an embodiment, the magnitude of the average compressive stress in the first glass substrate 410 is less than the average compressive stress in the second glass substrate 420 due to the indirect connection between the first glass substrate 410 and the third glass substrate 430. In an embodiment, each of the first glass substrate 410 and the second glass substrate 420 includes an average compressive stress greater than or equal to 5 MPa and less than or equal to 40 MPa.

[0124] This article Figure 3 Compared to the glass-polymer laminate 300, the glass-polymer laminate 400 may provide further improved impact performance. The additional polymer layer (the first polymer layer 415 disposed between the first glass substrate 410 and the second glass substrate 420) may make damage caused by micro-impacts less severe due to its local deformation (thereby attenuating the energy associated with the impact). It is believed that the additional polymer layer provides an additional glass-polymer interface through which cracks must propagate to reach the tensile third glass substrate 430, thereby increasing the damage threshold of the diffusion defect. In an embodiment, the combined outer glass substrate thickness of the glass-polymer laminate 400 (i.e., the sum of thicknesses 412 and 422) may be greater than that of the previous embodiment. Figure 3 The first glass substrate 310 has a thickness of 50. Thus, compared to the glass-polymer laminate 300, the glass-polymer laminate 400 may have a greater glass thickness that can be damaged without being noticeably damaged. It is believed that the glass-polymer laminate 400 may provide a greater glass thickness than the glass-polymer laminate described herein. Figure 3 Certain embodiments of the glass-polymer laminate 300 described herein have improved impact performance, particularly when the combined outer glass substrate thickness is greater than 50 μm.

[0125] In embodiments, the presence of multiple polymer layers can eliminate the need for CTE-induced compressive stresses in the glass-polymer laminate 400. That is, embodiments are contemplated in which the glass-polymer laminate 400 is constructed to not contain CTE-induced compressive stresses (e.g., the glass substrates can be composed of glasses with similar CTEs, or the stack may not be heated or cooled to curing temperatures during lamination). In such embodiments, it is believed that the multiple adhesive layers will function to absorb damage, as well as provide a mechanism for preventing impact-induced damage from propagating to the third glass substrate 430.

[0126] In embodiments, it is believed that defects caused by impact in the second glass substrate 420 will be particularly difficult to see, particularly when the first polymer layer 415 and the second polymer layer 425 are selected to have a refractive index that substantially matches the refractive index of the second glass substrate 420, as described herein. Therefore, it is believed that the glass-polymer laminate 400 can allow for absorption of a wider range of impact events than the glass-polymer laminate 300 without degrading the optical performance of the window 24 to a significant extent.

[0127] Although this article Figure 4 The described embodiment includes only two relatively thin outer glass substrates, but it should be understood that embodiments including more outer glass substrates (e.g., 3, 4, 5, 6, 7 or even more outer glass substrates) are also contemplated and within the scope of the present disclosure. In such embodiments, each outer glass substrate may be similar in composition and structure to those described herein. Figure 3 1 and 2. The first outer glass substrate 310 is similar to that described herein. If four or more outer glass substrates are included, the glass-polymer laminate may not include a relatively thick inner glass substrate. Such an embodiment may not include CTE-induced compressive stresses in any layer because the number of polymer layers present may provide sufficient impact performance. Eliminating CTE-induced compressive stresses may also eliminate warping issues. It should be understood that increasing the number of polymer layers in the glass-polymer laminates described herein may adversely affect light transmittance, making such laminates unsuitable for certain applications.

[0128] Reference now Figure 5 , according to an example embodiment, a curved glass-polymer laminate 500 is schematically depicted. In an embodiment, the curved glass-polymer laminate 500 may replace the glass-polymer laminate described herein. Figure 3 The glass-polymer laminate 300 is used as the window 24 of the LiDAR system 12 (see Figure 2 ). The glass-polymer laminate 500 is depicted as including a first glass substrate 510, a first polymer layer 515, and a second glass substrate 520. The curved glass-polymer laminate 500 may be generally described herein. Figure 3 The glass-polymer laminate 300 is described as having a similar structure and formed using similar techniques (e.g., such that the thicknesses 512, 516, and 522 of the first glass substrate 510, the first polymer layer 515, and the second glass substrate 520 correspond to the thicknesses 50, 56, and 52, respectively). In an embodiment, the first glass substrate 510 and the second glass substrate 520 include similar thicknesses and compositions as the first glass substrate 310 and the second glass substrate 320, with the difference that the first glass substrate 510 and the second glass substrate 520 may only be pre-formed (e.g., via a suitable thermoforming process) to have the described curved shape. Embodiments are also contemplated in which at least one of the first glass substrate 510 and the second glass substrate 520 is cold-formed into a non-planar shape.

[0129] In an embodiment, although the first glass substrate 510 and the second glass substrate 520 are initially flat prior to lamination, during the lamination process described herein, the warping of the curved glass-polymer laminate 500 is utilized to form the curved shape. In such an embodiment, the thickness 522 of the second glass substrate 520 may be less than 50 mm as described herein. Figure 3 The second glass substrate 320. In an embodiment, the thickness 522 is less than or equal to 1.5 mm (e.g., less than or equal to 1.4 mm, less than or equal to 1.3 mm, less than or equal to 1.2 mm, less than or equal to 1.1 mm, less than or equal to 1.0 meter) and greater than or equal to 100 μm. Due to the different volume shrinkage during heating or cooling after the first polymer layer 515 is cured, the second glass substrate 520, when composed of a higher CTE glass, shrinks more than the first glass substrate 510. The bonding with the first glass substrate 510 suppresses the shrinkage of the second glass substrate 520 to a certain extent, resulting in a strain distribution in the second glass substrate 520. The reduction in the thickness of the second glass substrate 520 reduces the stiffness of the second glass substrate 520, resulting in the strain distribution manipulating the shape of the second glass substrate 520. The bonding between the first glass substrate 510 and the second glass substrate 520 causes the first glass substrate 510 to bend together with the second glass substrate 520.

[0130] The thickness and composition of the first glass substrate 510 and the second glass substrate 520 may be selected so that the warping provides the desired curvature. It may be beneficial to have the outer surface 44 be convex in shape because an impacting object may be directed away from the line of sight of the LiDAR system 12 (see Figure 2 ). The convex shape can also be used to focus the emitted radiation 22 or the reflected radiation 28.

[0131] In an embodiment, the first glass substrate 510 includes a compressive stress from a CTE mismatch between the first glass substrate 510 and the second glass substrate 520. For example, the first glass substrate 510 may include an average compressive stress greater than or equal to 5 MPa and less than or equal to 40 MPa, while the second glass substrate 520 may include an average tensile stress less than or equal to 10 MPa. The curved glass-polymer laminate 500 may provide the impact performance benefits described herein while having a curved shape caused by warpage that is suitable for a particular application.

[0132] Example

[0133] Embodiments of the present disclosure may be further understood according to the following examples.

[0134] The measurements were similar to those in this paper. Figure 3-5 The light transmittance of glass-polymer laminates composed of the described materials was measured and compared with various monolithic glass sheets to determine the suitability of the glass-polymer laminates described herein for various sensor applications. Figure 6 The measured light transmittance results are described. The glass-polymer laminates measured consisted of a 1.5 mm thick inner glass substrate composed of an aluminosilicate composition (without IOX) disposed between two Corning Eagle 45CPS Stone Chip Windshield Repair Resin ("UB45") produced by Ultra Bond was used for the polymer layer separating the inner glass substrate from the outer glass substrate. The laminate was cured at 100°C and then cooled to room temperature, causing the outer glass substrate to exhibit compressive stress. As shown in the figure, the glass-polymer laminate exhibited the same compressive stress as aluminosilicate and Corning Eagle The monolithic glass sheets composed of the composite have comparable light transmittance performance. As shown in the figure, the light transmittance of the laminate is greater than 91% from 400 nanometers to 1650 nanometers, including the wavelength ranges adjacent to 905 nanometers and 1550 nanometers. Such results demonstrate the suitability of the glass-polymer laminate described herein for use in LiDAR systems.

[0135] Examples 1 and 2

[0136] A pair of polymer-glass laminates were produced, each glass laminate comprising two 2.1 mm thick outer glass layers formed of soda-lime glass with a UB45 polymer layer bonded therebetween. Example 1 was cured at room temperature, while Example 2 was cured at a cure temperature of 100°C. The laminates were then subjected to sharp impact testing using sandpaper. Specifically, a ball structure was guided down a tube and dropped onto the article from a height of 8 inches with one of the glass layers in contact with 120 grit sandpaper (the sandpaper was in contact with the side of the glass article not contacted by the ball). The results are shown in Figure 7 , the image on the left depicts a portion of Example 1 and the image on the right depicts a portion of Example 2. As shown, the fractures resulting from impact testing are highly visible regardless of the cure temperature. In these examples, the relatively thick outer layer causes the fracture to be distorted out of plane with high reflectivity, thereby increasing the visibility of the fracture. The size of the fracture is several hundred microns, which will greatly affect the optical performance of any sensor that incorporates the laminate as a protective window. It is believed that the poor impact performance is due to the thick outer layer and the lack of compressive stress in the laminate (which comes from the glass substrate of the same composition).

[0137] Examples 3 and 4

[0138] A pair of glass-polymer laminates are prepared, each glass-polymer laminate comprising a Eagle The laminates were formed of an outer glass layer of 0.2 mm thick formed of 1.5 mm glass and an inner glass layer of 2.1 mm thick formed of soda-lime glass. The polymer layer between the glass layers was formed of UB45. Example 3 was cured at room temperature, while Example 4 was cured at a curing temperature of 100°C. The laminates were then subjected to a sharp impact test using sandpaper. The results were Figure 8 , the left image depicts a portion of Example 3 and the right image depicts a portion of Example 4. Both examples show a clear improvement over Examples 1 and 2. The relatively thin outer glass layer prevents the fracture from twisting out of plane and thus becoming visible. In addition, the compressive stress generated by the elevated curing temperature in Example 4 further reduces the visibility of the damage by keeping the fracture closed.

[0139] Examples 5 and 6

[0140] Example 5 is a symmetrical glass-polymer laminate comprising two Eagle The glass is formed into an outer glass layer of 0.2 mm thick and a soda-lime glass inner glass layer of 2.1 mm thick. Two UB45 polymer layers are arranged between the glass layers. Example 6 is an asymmetric glass-polymer laminate having a structure similar to that described herein. Figure 4The glass-polymer laminate 400. Two Eagle An outer glass layer of 0.1 mm thick was formed of glass and disposed on a 2.1 mm thick inner glass layer of soda lime glass. Two UB45 polymer layers were disposed between the glass layers. Examples 5 and 6 were cured at 100°C. The laminates were then subjected to sharp impact testing using sandpaper. The results are shown in Fig. 9 , the left image depicts a portion of Example 5 and the right image depicts a portion of Example 6. It can be seen that the asymmetric laminate structure appears to provide comparable results to the symmetric laminate structure in terms of visibility of the fracture. In both cases, the relatively thick inner glass layer was not damaged.

[0141] As can be seen by comparing Example 4 and Example 6, the asymmetric laminate having multiple relatively thin outer glass layers exhibits significantly less visible damage. It is believed that this is due to the compressive stresses in the thin layers and the deformation of the additional bonding material to prevent the propagation of the fracture. It is also important to note that the damage to the second outer glass layer (the thin outer glass layer that was not directly impacted) was mostly suppressed, and the damage in this layer was mostly invisible to the naked eye. These results demonstrate the efficacy of incorporating additional thin outer glass layers in further suppressing damage caused by impact.

[0142] Example 7-12

[0143] The following six laminate structures were constructed by creating stacks of the following glass layer configurations with UB45 bonding layers between the glass layers (each sample was 5.08 cm x 5.08 cm in size):

[0144] Example 7: 0.1mm EXG, 0.1mm EXG, 2.1mm SLG;

[0145] Example 8: 0.2mm EXG, 0.2mm EXG, 2.1mm SLG;

[0146] Example 9: 0.1mm EXG, 2.1mm SLG, 0.1mm EXG;

[0147] Example 10: 0.1mm EXG, 2.1mm SLG;

[0148] Example 11: 0.2mm EXG, 2.1mm SLG;

[0149] Example 12: 0.2mm EXG, 2.1mm SLG, 0.2mm EXG;

[0150] Where EXG represents Eagle glass, SLG stands for soda lime glass. Each of Examples 7-12 was heated to a curing temperature of 100°C and the UB45 adhesive layer was cured with UV light.

[0151] Then use Fig.10 The experimental setup described in was used to perform dynamic damage introduction testing on each example. As shown, a variable speed impactor 1000 is positioned on a modular impactor holder 1002 to impact a sample 1004. The variable speed impactor 1000 includes a Vickers diamond indenter. A velocity gate 1006 is positioned just upstream of the sample 1004 so as to measure the velocity of the impactor 1000 just before impacting the sample 1004. The sample 1004 is positioned to contact a triaxial compressive charge cell 1008, which is capable of measuring loads up to 4400N at a sampling rate of 200kHz. The following method was used to test each sample of Examples 7-12: Each sample 1004 was subjected to up to five indentations at a given velocity (800mm / sec, 1000mm / sec, 1250mm / sec, 1500mm / sec, 2000mm / sec, 2500mm / sec). If the damage at the center of sample 1004 is not obvious in the first impact event, additional indentations are present at 12 o'clock, 3 o'clock, 6 o'clock, and 9 o'clock positions approximately 2500 μm from the center. The sample is evaluated for impact severity at each impact velocity.

[0152] The results of Example 7 are described in Fig.11 and are summarized in Table 1 below:

[0153] Table 1

[0154] Impact speed (m / s) Impact load(N) 800 840.39 800 1312.95 800 1297.05 1000 960.49 1250 1286.38

[0155] The results of Example 8 are described in Fig.12 and are summarized in Table 2 below:

[0156] Table 2

[0157] Impact speed (m / s) Impact load(N) 800 867.92 800 1317.47 800 1356.57 800 1649.16 800 1478.32 1000 1878.13 1250 1893.80 1250 1930.18

[0158] The results of Example 9 are described in Fig.13 and are summarized in Table 3 below:

[0159] Table 3

[0160] Impact speed (mm / s) Impact load(N) 800 1104.98 800 1658.91 800 1618.23 1200 1638.26 1000 1050.25 1200 1034.50

[0161] The results of Example 10 are described in Fig.14 and are summarized in Table 4 below: Table 4

[0162] Impact speed (mm / s) Impact load(N) 800 803.435 800 803.027 800 759.032 1000 1005.506 1250 1280.471 1600 1547.249 2000 1946.995

[0163] The results of Example 11 are described in Fig.15 and are summarized in Table 5 below: Table 5

[0164] Impact speed (mm / s) Impact load(N) 800 813.027 800 813.058 800 815.894 800 809.429 800 795.051 1000 1009.57 1250 1275.65 1000 1007.671

[0165] The results of Example 12 are described in Fig.16 and are summarized in Table 6 below: Table 6

[0166]

[0167]

[0168] like Figure 11-16 As shown in Tables 1-6, the examples having an asymmetric structure including a thin outer glass layer disposed on one side of a thick inner glass layer (the thin outer glass layer is directly impacted) appear to exhibit superior impact performance. Notably, Example 10, which includes only a relatively thin outer glass substrate, did not fail or break at impact speeds of 1600 mm / sec and 2000 mm / sec. Fig.14 As shown in the rightmost image included in the , the approximate diameter of the defect produced at 2000 mm / sec is about 1000 μm, while each of the other examples, when tested at speeds exceeding 1200 mm / sec, either exhibited a much larger defect or shattered completely. At the lower impact speed of 800 mm / sec, the examples having multiple relatively thin outer glass layers disposed to one side of the inner glass layer (Examples 7 and 8) had superior performance, with substantially smaller defect sizes at comparable load levels. It is also noteworthy that each of Examples 7-12 performed superior to monolithic glass, which was found to typically fail at speeds of 500 mm / sec or less.

[0169] These results demonstrate that the glass-polymer laminates described herein can withstand a wider variety of impact events than existing monolithic cover windows without experiencing complete through cracking. In addition, damage caused by certain impact events can be reduced due to the flexibility of the relatively thin outer glass layer and the compressive stresses therein, as well as the polymer layer preventing defects from reaching the relatively thick inner glass layer.

[0170] It will be apparent to those skilled in the art that various modifications and variations can be made without departing from the spirit or scope of the claims.

Claims

1. A product, comprising: The first glass substrate has a thickness t G1 and the coefficient of thermal expansion CTE G1 ; The second glass substrate has a thickness t G2 and the coefficient of thermal expansion CTE G2 ; as well as A first polymer layer, the first polymer layer is disposed between the first glass substrate and the second glass substrate, the first polymer layer having a thickness t P1 and the coefficient of thermal expansion CTE P1 , in: The first glass substrate comprises a compressive stress, |CTE G1 -CTE G2 |>0.5ppm / ℃, t G2 Greater than 2.0 mm, and t G1 Less than or equal to 300μm.

2. The article of claim 1, wherein: t G1 Less than or equal to 200 μm, and t G2 Greater than 2.5mm and less than or equal to 3.8mm.

3. The article of claim 2, wherein: The compressive stress is greater than or equal to 5 MPa and less than or equal to 40 MPa, and The second glass layer comprises a tensile stress less than or equal to 10 MPa.

4. The article of any one of claims 1 to 3, wherein: t G1 Less than or equal to 150 μm, and t G2 Greater than or equal to 2.5 mm and less than or equal to 3.8 mm.

5. The article of any one of claims 1-4, wherein the first glass substrate is formed from a glass that exhibits abnormal fracture behavior when subjected to a Vickers diamond indenter test.

6. The article of any one of claims 1-5, wherein the first glass substrate is not chemically strengthened and the compressive stress is generated by laminating the first glass substrate to the second glass substrate via the first polymer layer at a curing temperature that is at least 20° C. different from a use temperature of the article.

7. The article of any one of claims 6, wherein CTE G1 <CTE G2 , and the curing temperature is greater than or equal to 30°C.

8. The article of any one of claims 1-7, wherein the second glass substrate comprises soda-lime glass.

9. The article of claim 1, further comprising: The third glass substrate has a thickness t G3 and the coefficient of thermal expansion CTE G3 ,as well as A first polymer layer is disposed between the first glass substrate and the third glass substrate, and the first polymer layer has a thickness t P2 and the coefficient of thermal expansion CTE P2 ,in: The second glass substrate comprises a second compressive stress, |CTE G2 -CTE G3 |>0.5ppm / ℃, and t G3 Less than or equal to t G2 20% of.

10. The article of claim 9, wherein t G1 and t G3 Both are less than or equal to 200 μm.

11. The article of claim 10, wherein t G2 Greater than or equal to 2.5 mm and less than or equal to 3.8 mm.

12. The article of claim 9, wherein the first glass substrate and the second glass substrate are formed of the same glass composition such that CTE G2 =CTE G3 .

13. The article of claim 9, wherein t G1 =t G3 , and t G1 and t G3 Both are less than or equal to 150μm.

14. The article of any one of claims 1-13, wherein the total thickness of the article is less than or equal to 4.0 mm.

15. The article of any one of claims 1-14, wherein the article does not break when the first glass substrate is impacted by a Vickers diamond indenter traveling at a speed of 1000 mm / sec.

16. The article of any one of claims 1-15, wherein at least one of the first glass substrate and the second glass substrate warps as a result of laminating the first glass substrate to the second glass substrate via the first polymer layer.

17. A sensor, comprising: shell; a detection element, wherein the detection element is disposed in the housing; as well as a window attached to the housing so as to surround an interior of the housing, wherein the window comprises: The first glass substrate has a thickness t G1 and the coefficient of thermal expansion CTE G1 ; The second glass substrate has a thickness t G2 and the coefficient of thermal expansion CTE G2 ;as well as A first polymer layer is disposed between the first glass substrate and the second glass substrate, and the first polymer layer has a thickness t P1 and the coefficient of thermal expansion CTE P1 , in: The first glass substrate includes a compressive stress greater than or equal to 5 MPa and less than or equal to 40 MPa, wherein the compressive stress is determined by CTE G1 With GTE G2 The difference between t G1 Less than or equal to 300 μm, and t G2 Greater than 2.0mm.

18. The sensor of claim 17, wherein: t G1 Less than or equal to 200 μm, and t G2 Greater than or equal to 2.5 mm and less than or equal to 3.8 mm.

19. The sensor according to any one of claims 17-18, wherein: The first glass substrate is formed of a glass that exhibits abnormal fracture behavior when subjected to a Vickers diamond indenter test, and The first glass substrate forms an outer surface of the window, which is exposed to the environment outside the housing.

20. The sensor of any one of claims 17-19, wherein the first glass substrate is not chemically strengthened and the compressive stress is generated by laminating the first glass substrate to the second glass substrate via the polymer layer at a curing temperature greater than or equal to 50°C.

21. The sensor of any one of claims 17-20, further comprising: The third glass substrate has a thickness t G3 and the coefficient of thermal expansion CTE G3 ,as well as A first polymer layer is disposed between the first glass substrate and the third glass substrate, and the first polymer layer has a thickness t P2 and the coefficient of thermal expansion CTE P2 ,in: The second glass substrate comprises a second compressive stress, |CTE G2 -CTE G3 |>0.5ppm / ℃, and t G3 Less than or equal to t G2 10% of.

22. The sensor of claim 21, wherein t G1 and t G3 Both are less than or equal to 200 μm.

23. The sensor of claim 22, wherein t G2 Greater than or equal to 2.5 mm and less than or equal to 3.8 mm.

24. The sensor of claim 21, wherein the first glass substrate and the third glass substrate are formed of the same glass composition such that CTE G1 =CTE G3 .

25. The sensor of any one of claims 21 to 24, wherein t G1 =t G3 , and t G1 and t G3 Both are less than or equal to 150μm.

26. A method comprising: Disposing a first polymer layer between a first glass substrate and a second glass substrate, wherein the thickness of the first glass substrate is less than or equal to 15% of the thickness of the second glass substrate, and wherein the thickness of the second glass substrate is greater than 2.0 mm; At the curing temperature T C curing the first polymer layer in an environment of 100 to form an article; as well as After the curing step, the temperature of the first glass substrate and the second glass substrate is returned to a use temperature, the use temperature being greater than or equal to 0° C. and less than or equal to 30° C., wherein: The first thermal expansion coefficient of the first glass substrate differs from the second thermal expansion coefficient of the second glass substrate by at least 0.5 ppm / °C, and T C The difference from the use temperature is at least 20° C., so that returning the temperature to the use temperature causes the first glass substrate to have a compressive stress greater than or equal to 8 MPa and less than or equal to 40 MPa.

27. The method of claim 26, further comprising: Prior to the curing step, a second polymer layer is disposed between the first glass substrate and a third glass substrate, wherein the thickness of the third glass substrate is less than or equal to 10% of the thickness of the second glass substrate.

28. The method of claim 27, wherein a third coefficient of thermal expansion of the third glass substrate differs from the second coefficient of thermal expansion by at least 0.5 ppm / °C such that after returning to the use temperature, the third glass substrate comprises a second compressive stress.

29. The method of any one of claims 27-28, wherein the third glass substrate and the first glass substrate comprise the same thickness and are formed of the same glass composition.

30. The method of any one of claims 27-29, wherein the first glass substrate and the third glass substrate are both formed of glasses that exhibit abnormal fracture behavior when subjected to a Vickers diamond indenter test.

Citation Information

Patent Citations

  • Ion exchangeable glass with high crack initiation threshold

    US20130122284A1

  • Alkali-free glasses containing iron and tin as fining agents

    US7534734B2

  • Fining of boroalumino silicate glasses

    US7851394B2

  • US2020/35034

  • US2020/35497